A Precision Instrument for the Clinical Measurement of Stereoscopic Acuity - Larson, William L; Giroux, Roland (Canadian Journal of Optometry, 1982)
When tested by different methods, a patient's stereoscopic acuity is seldom the same. This raises the question as to which one gives the true stereoscopic acuity. To answer this, a programmable test for stereoscopic acuity was designed to serve as a testing standard. This is described and a comparative study with it and four other tests is reported.